Аnalysis of the competitiveness of hotels in the Republic of Kazakhstan - Tleuberdinova, A. T.; Ussenov, M.М.; Ussenova, D.M. (KSU Publ., 2013)
Hospitality is an integral part of tourism industry development. The state and level of development of the hotel industry affects the level of the flow of domestic and inbound tourism. In this article the main directions of development of the modern hotel business has been analyzed in the Republic of Kazakhstan. The article discusses the relevance of hotel industry in the Republic of Kazakhstan, the segmentation of accommodation and categories. the competitiveness of hotels. In this article the basic performance of the hotels in the Republic of Kazakhstan has been identified.
Қазақстан Республикасында қонақ үй шаруашылығының бəсекеқабілеттілігін талдау
Анализ конкурентоспособности гостиничного хозяйства в Республике Казахстан
Keywords: tourism; hotel industry; hotel services; hotel enterprises; accommodation; category of hotel companies; swot analysis; competitiveness